The Companion Village Project : An Extension Education Tool for Improving Crop Production - Gabriel Malima; Roger Blomquist; Kent Olson; Michael Schmitt (Journal of International Agricultural and Extension Education, 2014)
To address the issue of farmers not knowing or adopting improved crop production practices, the Institute of Agriculture at the University of Iringa(formerly Tumaini University)in Iringa, Tanzania, developed the Companion Village Project (CVP). Working primarily with pastors at local churches, the CVP has 47 demonstration plots highlighting improved production practices and serving as a backdrop for multiple educational presentations throughout the growing season. Local farmers managed the CVP plots. Local farmers were able to see the results and discuss the improved practices with the pastors and other local leaders as well as with Institute staff. To estimate the impact of the CVP, yields were measured on the plots and surveys were taken of participating and non-participating farmers .Crop yields were greater with the recommended improved production practices compared to conventional practices. The visibility of the improved practices and greater yields has resulted in adoption of the improved practices by more farmers in the region
Keywords: Tanzania; agriculture; extension; training and visit; farmer field schools; demonstration plots